Hydrogenotrophs-Based Biological Biogas Upgrading Technologies - Antukh, Tatsiana; Lee, Ingyu; Joo, Sunghee; Kim, Hyunook (Frontiers in Bioengineering and Biotechnology, 2022)
Biogas produced from anaerobic digestion consists of 55–65% methane and 35–45% carbon dioxide, with an additional 1–2% of other impurities. To utilize biogas as renewable energy, a process called biogas upgrading is required. Biogas upgrading is the separation of methane from carbon dioxide and other impurities, and is performed to increase CH4 content to more than 95%, allowing heat to be secured at the natural gas level. The profitability of existing biogas technologies strongly depends on operation and maintenance costs. Conventional biogas upgrading technologies have many issues, such as unstable high-purity methane generation and high energy consumption. However, hydrogenotrophs-based biological biogas upgrading offers an advantage of converting CO2 in biogas directly into CH4 without additional processes. Thus, biological upgrading through applying hydrogenotrophic methanogens for the biological conversion of CO2 and H2 to CH4 receives growing attention due to its simplicity and high technological potential. This review analyzes the recent advance of hydrogenotrophs-based biomethanation processes, addressing their potential impact on public acceptance of biogas plants for the promotion of biogas production.